2022
DOI: 10.1021/acs.biochem.2c00083
|View full text |Cite
|
Sign up to set email alerts
|

Improved Repeat Protein Stability by Combined Consensus and Computational Protein Design

Abstract: High protein stability is an important feature for proteins used as therapeutics, as diagnostics, and in basic research. We have previously employed consensus design to engineer optimized Armadillo repeat proteins (ArmRPs) for sequence-specific recognition of linear epitopes with a modular binding mode. These designed ArmRPs (dArmRPs) feature high stability and are composed of M-type internal repeats that are flanked by N-and C-terminal capping repeats that protect the hydrophobic core from solvent exposure. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…4 ), and affinity determination by FP resulted in a highly similar K d to the peptide (KR) 5 : 36.1 ± 2.9 nM for N Y M 4 C versus 30.5 ± 2.3 nM for N A M 4 C (mean ± S.D.) 14 . This combined evidence clearly demonstrates that the two protein variants respond almost identically to peptide binding, and data below therefore mostly describe structures employing the new N-cap.…”
Section: Resultsmentioning
confidence: 89%
See 3 more Smart Citations
“…4 ), and affinity determination by FP resulted in a highly similar K d to the peptide (KR) 5 : 36.1 ± 2.9 nM for N Y M 4 C versus 30.5 ± 2.3 nM for N A M 4 C (mean ± S.D.) 14 . This combined evidence clearly demonstrates that the two protein variants respond almost identically to peptide binding, and data below therefore mostly describe structures employing the new N-cap.…”
Section: Resultsmentioning
confidence: 89%
“…Biochemical data indicated that the original y east-derived N Y -terminal cap possesses an intrinsic instability against E. coli proteases, likely due to insufficient packing of the cap against the M1 module. The redesigned N-cap, described in Michel et al 14 and referred to as N A ( a rtificial), displayed improved stability and yielded very similar CSPs. A comparison of CSPs between N Y M 4 C and N A M 4 C upon binding (KR) 4 revealed similar binding for both constructs (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Conserved amino acids may replace non-conserved amino acids to obtain more stable variants ( Steipe, 1999 ; Porebski and Buckle, 2016 ). This method has been proven relatively reliable for improving protein thermostability ( Wojcik et al, 2019 ; Hayashi et al, 2022 ; Michel et al, 2023 ). Sequences whose query identity was above 30% and below 90% are screened for the alignment of the T7RNAP homologs ( Bendl et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%